2010
DOI: 10.1088/0268-1242/26/1/014026
|View full text |Cite
|
Sign up to set email alerts
|

The QD-Flash: a quantum dot-based memory device

Abstract: We demonstrate the large potential of III-V compound semiconductors for a novel type of Flash memory. The concept is based on self-organized III-V quantum dots (QDs). Here the advantages of the most important semiconductor memories, the dynamic random access memory and the Flash are merged. A non-volatile memory with fast access times (<10 ns) and good endurance (>10 15 write/erase cycles) as an ultimate solution seems possible. A storage time of 1.6 s at 300 K in InAs/GaAs QDs with an additional Al 0.9 Ga 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 29 publications
0
70
0
3
Order By: Relevance
“…5 The exclusive confinement of holes and their large localization energy makes GaSb/GaAs QDs particularly interesting for charge storage devices. [6][7][8] GaSb/GaAs QDs were first grown using molecular beam epitaxy 2,9 and later by metal-organic chemical vapor epitaxy, 10,11 followed by optical characterization, 9,[12][13][14][15] cross-section scanning electron microscopy investigations, 16 and deep-level transient spectroscopy (DLTS) studies, 17,18 accompanied by numerical calculations. [19][20][21] The various investigations have been performed on different samples.…”
Section: Introductionmentioning
confidence: 99%
“…5 The exclusive confinement of holes and their large localization energy makes GaSb/GaAs QDs particularly interesting for charge storage devices. [6][7][8] GaSb/GaAs QDs were first grown using molecular beam epitaxy 2,9 and later by metal-organic chemical vapor epitaxy, 10,11 followed by optical characterization, 9,[12][13][14][15] cross-section scanning electron microscopy investigations, 16 and deep-level transient spectroscopy (DLTS) studies, 17,18 accompanied by numerical calculations. [19][20][21] The various investigations have been performed on different samples.…”
Section: Introductionmentioning
confidence: 99%
“…Fast carrier capture and long charge storage capabilities of type-II QDs suggest their potential application in memory devices. 1,2 Recent studies have shown that the use of a two-dimensional electron 3,4 or hole 5,6 gas in combination with QDs allows writing and reading information, demonstrating the basic operations required in memory devices.…”
mentioning
confidence: 99%
“…Room temperature operation may be realized by tuning the material compositions of the QDs and the surrounding layers. 50 Hence for the desired room temperature operation, devices based on other material compositions (different Al contents etc.) need to be designed, fabricated and tested.…”
Section: Discussionmentioning
confidence: 99%